1993
DOI: 10.1136/oem.50.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Markers of early renal changes induced by industrial pollutants. III. Application to workers exposed to cadmium.

Abstract: Cadmium (Cd) was the third heavy metal investigated in the European collaborative research project on the development and validation of new markers of nephrotoxicity. Fifty workers exposed to Cd and 50 control workers were examined. After application of selection criteria 37 workers (mean age 43) exposed to Cd for an average of 11-3 years; and 43 age matched referents were retained for final analysis. The average concentrations of Cd in blood (Cd-B) and urine (Cd-U) of exposed workers were 5-5 pg Cd/l and 5-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Elevations in enzymes primarily of renal tubular origin, such as N-acetyl-β-Dglucosaminidase (NAG) and alanine aminopeptidase (AAP), have been observed at occupational cadmium exposures of 3.7-6.3 µg urinary cadmium/g creatinine (2,4,7). Increases in these enzymes have been associated with chemical-induced renal tubular damage (8,9) Most studies of cadmium-induced renal effects using these and other biomarkers have been conducted among individuals with occupational or high environmental exposures (4,7,(10)(11)(12)(13)(14)(15)(16). Results of a national health survey indicate that the geometric mean value (and 95th percentile) for urinary cadmium among the U.S. general population age 6 years or older is approximately 0.27 (1.48) µg/g creatinine (17), but little information is available on renal effects that may occur in people with urinary cadmium levels < 2 µg/g.…”
mentioning
confidence: 99%
“…Elevations in enzymes primarily of renal tubular origin, such as N-acetyl-β-Dglucosaminidase (NAG) and alanine aminopeptidase (AAP), have been observed at occupational cadmium exposures of 3.7-6.3 µg urinary cadmium/g creatinine (2,4,7). Increases in these enzymes have been associated with chemical-induced renal tubular damage (8,9) Most studies of cadmium-induced renal effects using these and other biomarkers have been conducted among individuals with occupational or high environmental exposures (4,7,(10)(11)(12)(13)(14)(15)(16). Results of a national health survey indicate that the geometric mean value (and 95th percentile) for urinary cadmium among the U.S. general population age 6 years or older is approximately 0.27 (1.48) µg/g creatinine (17), but little information is available on renal effects that may occur in people with urinary cadmium levels < 2 µg/g.…”
mentioning
confidence: 99%
“…This indicates that both B-Cd and U-Cd are valid as indicators of long-term environmental exposure of the general population to cadmium. Several studies have supported this assumption and the close correlation between B-Cd and U-Cd in such circumstances (Liu et al 2001;Moon et al 1999;Roels et al 1993). In fact, many years after an exposure, B-Cd is likely better than U-Cd as an indicator of previous exposure because if tubular damage has occurred, U-Cd measurements may be difficult to interpret (Börjesson et al 2001;Ikeda et al 1999;Järup et al 2000).…”
Section: Case Discussionmentioning
confidence: 77%
“…Through the use of biomarkers of damage to various parts of the nephron, a pattern of damage is emerging that is consistently observed now both in U.S. and European studies of men occupationally exposed to cadmium (4)(5)(6)(7)(8)(9)(10) The lowest observed effect is indicated by a significant prevalence of abnormal 6-keto-prostaglandin Fla (6-keto-PGFi,a) and sialic acid levels in urine at an approximate urine cadmium concentration of 2.4 nmol Cd/mmol creatinine (2.4 pg Cd/g creatinine) (10). Proteins such as albumin and transferrin originate in the plasma and are filtered to a limited degree through the glomerulus, and the protein that is filtered is primarily reabsorbed by the tubules.…”
Section: Thresholds Of Effects: Cadmiummentioning
confidence: 99%
“…Some of these candidate markers are beginning to be examined in human studies. Excretion of fibronectin has been examined in relation to exposure to three heavy metals (cadmium, lead, and mercury), with no significant changes in excretion seen in the exposed groups (7)(8)(9).…”
Section: Potential New Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation